Full-torus impurity transport simulation in boron powder injection experiments in the Large Helical Device - M. Shoji; G. Kawamura; R. Smirnov; J. Romazanov; A. Kirschner; Y. Tanaka; S. Masuzaki; T. Kawate; F. Nespoli; R. Lunsford; E.P. Gilson; S. Brezinsek; et al. (Nuclear Materials and Energy, 2024)
The toroidal distribution of boron deposition on plasma-facing components (PFCs) in boron powder injection using an impurity power dropper (IPD) was investigated by full-torus simulation and observations in a systematic plasma density-scan experiment. The images of the ablation of dropped boron powders observed with a visible CCD camera were consistently explained by the simulations of the ablation positions of the boron powders considering the size distribution. Simulations assuming full-torus boron deposition on the PFCs did not reproduce the observed intensity profile of boron emission lines for higher plasma densities. It indicated that the density of boron deposited on PFCs installed toroidally far from the IPD was low for higher plasma densities due to the change in the ablation positions of the boron powders toward the outboard side. The experimental results verified the previous full-torus simulation of the toroidal distribution of the boron deposition in both lower and higher plasma densities.